Alterations of circulating NUCB2/nesfatin-1 during short term therapeutic improvement of anxiety in obese inpatients. (May 2017) - Hofmann, Tobias; Weibert, Elena; Ahnis, Anne; Obbarius, Alexander; Elbelt, Ulf; Rose, Matthias; Klapp, Burghard F.; Stengel, Andreas
Highlights: NUCB2/nesfatin-1 is regulated in a sex-dependent manner. Women show higher levels of anxiety than men. NUCB2/nesfatin-1 does not change following therapeutic improvement of anxiety. Abstract: In addition to its anorexigenic properties in the neuroendocrine regulation of hunger and satiety, mounting evidence indicates a role for NUCB2/nesfatin-1 in the regulation of emotional stress responses which seems to occur in a sex-specific way. In the present study, we investigated the association of NUCB2/nesfatin-1 plasma levels with anxiety, depressiveness and perceived stress in obese men and women and their alterations during inpatient treatment. We expected a decrease of NUCB2/nesfatin-1 levels in female and an increase in male patients reporting a relevant alleviation of anxiety. We analyzed 69 inpatients (44 female, 25 male; body mass index, mean: 50.2 ± 9.5 kg/m 2, range: 31.8–76.5 kg/m 2 ; mean age: 45.0 ± 12.4 years) hospitalized due to morbid obesity with mental (not necessarily anxiety disorders) and somatic comorbidities. NUCB2/nesfatin-1 plasma levels were measured by ELISA. Anxiety (GAD-7), depressiveness (PHQ-9) and perceived stress (PSQ-20) were concurrently determined as patient-reported outcomes. All measurements were carried out at the initiation of and during inpatient treatment when a clinically meaningful improvement of anxiety was achieved (≥5 points on GAD-7) or missed (±1 point). NUCB2/nesfatin-1 was positively correlated with anxiety scores in women at the beginning of ( r  = 0.411; p  = 0.006) and during ( r  = 0.301; p  = 0.047) inpatient treatment. In men, a significant negative correlation was observed following treatment ( r  = −0.469; p  = 0.018), while at the outset of treatment only a trend was observed ( r  = −0.381; p  = 0.059). Unexpectedly, neither women (n = 19; at beginning vs. during treatment; 0.49 ± 1.00 ng/ml vs. 0.38 ± 0.72 ng/ml; p  = 0.687) nor men (n = 9; 0.17 ± 0.31 ng/ml vs. 0.19 ± 0.36 ng/ml; p  = 0.427) who improved in anxiety scores ( p <  0.001) displayed significant changes of NUCB2/nesfatin-1 plasma levels, although the direction of change was as expected with a decrease in women (−23.3%) and an increase in men (+12.4%). In addition, the change of NUCB2/nesfatin-1 was not explained by the course of anxiety (women: p  = 0.587; men: p  = 0.373). In conclusion, women and men showed an inverse association between NUCB2/nesfatin-1 and anxiety with a positive correlation in women and a negative correlation in men (although this correlation was not statistically significant in men at the beginning of treatment). However, no significant change of NUCB2/nesfatin-1 following improvement of anxiety has been observed. This might be due to the short observation interval, or due to too small anxiety improvements associated with too low baseline anxiety levels.